Popular opinion in totalitarian regimes : Fascism, Nazism, Communism - Corner, Paul, 1944- 1944- (Oxford Univ. Press, 2009)
"Fascism, Nazism, and Communism dominated the history of much of the twentieth century, yet comparatively little attention has focused on popular reactions to the regimes that sprang from these ideologies. Popular Opinion in Totalitarian Regimes is the first volume to investigate how ordinary people reacted to totalitarian rule in the Soviet Union, Fascist Italy, Nazi Germany, and the Communist regimes in Poland and East Germany after 1945."--BOOK JACKET.